The fractional Hartree equation without the Ambrosetti–Rabinowitz condition. (February 2017) - Francesconi, Mauro; Mugnai, Dimitri
Abstract: We consider a class of pseudo-relativistic Hartree equations in presence of general nonlinearities not satisfying the Ambrosetti–Rabinowitz condition. Using variational methods based on critical point theory, we show the existence of two non trivial signed solutions, one positive and one negative.